Jugoslovensko bankarstvo Journal: Insights into the Banking Sector of Serbia and Yugoslavia (1971–1992) - Slađana Sredojević; Vesna Aleksić (Токови историје)
Yugoslavia’s economy and banking sector underwent significant modifications as a result of constitutional amendments passed in the late 1960s that redefined commercial banks as universal financial institutions. These changes also established national banks in each republic and province, considerably limiting the power of the National Bank of Yugoslavia. The 1974 Constitution cemented these reforms and promoted an “agreement economy.” With the increasing autonomy of national banks, the National Bank’s power over monetary policy weakened. During this time, the Yugoslav Banks Association emerged as a prominent actor, actively tracking banking industry changes via publications such as Jugoslovensko bankarstvo (Yugoslav Banking). The journal provides valuable insights, particularly into the late 1980s, when banks began transitioning into joint-stock companies.